The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3113/fai.2012.0565
|View full text |Cite
|
Sign up to set email alerts
|

Lesser Metatarsophalangeal Instability: Presentation, Management, and Outcomes

Abstract: Painful MTP instability is a common cause of forefoot pain. Most patients can be treated nonoperatively. Operatively treated patients had no significant improvement in outcomes with regards to pain or function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
0
16
1
Order By: Relevance
“…Chronic physical stressors associated with lesser MTP instability include high heels, 5,27,30,38 a relatively long second metatarsal known as Morton’s toe, 9,13,29,31,37 and hallux valgus. 13,37 Additionally, in aged individuals, fat pad atrophy makes the joint more vulnerable.…”
Section: Etiology Of Lesser Mtp Instabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic physical stressors associated with lesser MTP instability include high heels, 5,27,30,38 a relatively long second metatarsal known as Morton’s toe, 9,13,29,31,37 and hallux valgus. 13,37 Additionally, in aged individuals, fat pad atrophy makes the joint more vulnerable.…”
Section: Etiology Of Lesser Mtp Instabilitymentioning
confidence: 99%
“…27,32 Of these joints, the second MTP is the most commonly affected. 30,38-40 Women and the elderly are the populations at highest risk. 4,13,27,30,32 The age range is wide, with a mean age of 60 years in the general population and 50 years in the athletic population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Myerson et al [6] reported the results of 64 feet treated with flexor digitorum longus tendon transfer for second MTP joint instability and stated that a substantial number of the patients remained dissatisfied, or satisfied with major reservations, because of residual stiffness of the toe, loss of active flexion, and generalized dysfunction of the toe. Peck et al [9] reported the results of 55 feet treated with lesser toe straightening, flexor to extensor tendon transfer, and Weil or Stainsby procedure for lesser MTP instability, and stated that operatively treated patients had no significant improvement in outcomes with regards to pain or function. Therefore, flexor to extensor tendon transfer for MTP joint instability may not provide a consistently successful outcome.…”
Section: Introductionmentioning
confidence: 97%
“…The primary surgical technique for subluxation and dislocation for the lesser MTP joints has been open reduction with a soft tissue release and stabilization with flexor to extensor tendon transfer [5,6,9]. Myerson et al [6] reported the results of 64 feet treated with flexor digitorum longus tendon transfer for second MTP joint instability and stated that a substantial number of the patients remained dissatisfied, or satisfied with major reservations, because of residual stiffness of the toe, loss of active flexion, and generalized dysfunction of the toe.…”
Section: Introductionmentioning
confidence: 99%